2015
DOI: 10.3390/bioengineering3010001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of Antibacterial Agents from Doped Halloysite Nanotubes

Abstract: The use of nanomaterials for improving drug delivery methods has been shown to be advantageous technically and viable economically. This study employed the use of halloysite nanotubes (HNTs) as nanocontainers, as well as enhancers of structural integrity in electrospun poly-e-caprolactone (PCL) scaffolds. HNTs were loaded with amoxicillin, Brilliant Green, chlorhexidine, doxycycline, gentamicin sulfate, iodine, and potassium calvulanate and release profiles assessed. Selected doped halloysite nanotubes (contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Its outer surface is mostly composed of SiO 2 and the inner surface of Al 2 O 3 , and, hence, those surfaces are oppositely charged [ 119 ]. The external siloxane and internal aluminol surface of halloysite is efficient as an absorbent (described above) or could be used as a carrier for drugs [ 120 , 121 , 122 , 123 ], nucleic acids [ 124 ], antibacterial agents [ 125 ], and antioxidants [ 119 , 126 , 127 , 128 , 129 , 130 ]. Therefore, halloysite is an efficient adsorbent both for cations and anions.…”
Section: Nano Approaches For Mycotoxin Risk Eliminationmentioning
confidence: 99%
“…Its outer surface is mostly composed of SiO 2 and the inner surface of Al 2 O 3 , and, hence, those surfaces are oppositely charged [ 119 ]. The external siloxane and internal aluminol surface of halloysite is efficient as an absorbent (described above) or could be used as a carrier for drugs [ 120 , 121 , 122 , 123 ], nucleic acids [ 124 ], antibacterial agents [ 125 ], and antioxidants [ 119 , 126 , 127 , 128 , 129 , 130 ]. Therefore, halloysite is an efficient adsorbent both for cations and anions.…”
Section: Nano Approaches For Mycotoxin Risk Eliminationmentioning
confidence: 99%
“…Due to the chemical makeup of the HNT lumen, it is capable of being doped with a diverse set of substances including antibiotics, chemotherapeutics, growth factors, RNA and DNA, and used as a vehicle for drug transportation and sustained release [20][21][22][23]. Additionally, several recent studies have demonstrated that HNTs are cytocompatible [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite has a molecular formula of Al 2 Si 2 O 5 (OH) 4 •nH 2 O ranging in the length from 0.2-2.0 µm. The inner and outer diameters of the halloysite nanotubes (HNTs) range from 15-50 nm and 30-50 nm respectively [31] with the difference in the inner and outer diameter imparting significant lumen space ranging from 10.7-39.0% [26]. In a recent publication by Liu and researchers [26], it has been stated that extensive research into the use of HNTs began in the 1940s and more recently it appears to be at the forefront of research partly due to the growing interest in tube-like nanoparticles.…”
Section: Introductionmentioning
confidence: 99%